2016
DOI: 10.1073/pnas.1601063113
|View full text |Cite
|
Sign up to set email alerts
|

Inferring responses to climate dynamics from historical demography in neotropical forest lizards

Abstract: We apply a comparative framework to test for concerted demographic changes in response to climate shifts in the neotropical lowland forests, learning from the past to inform projections of the future. Using reduced genomic (SNP) data from three lizard species codistributed in Amazonia and the Atlantic Forest (Anolis punctatus, Anolis ortonii, and Polychrus marmoratus), we first reconstruct former population history and test for assemblage-level responses to cycles of moisture transport recently implicated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 69 publications
(89 reference statements)
5
105
1
1
Order By: Relevance
“…A history of connections between western Amazonia and the Atlantic Forest, supported by our historical demographic study of B. bilineatus , was recovered by previous studies based on genetic data of birds and lizards (Batalha‐Filho et al., ; Prates et al., ). Phylogeographic studies have also found evidence of northern colonizations between the Atlantic Forest and northeastern Amazonia (Batalha‐Filho et al., ; Costa, ; Prates, Rivera, et al., ; Prates, Xue, et al., ). In spite of these two distinct proposed connection routes, previous studies have, by and large, found that Amazonia acted as the source of colonizations into the Atlantic Forest.…”
Section: Discussionmentioning
confidence: 98%
“…A history of connections between western Amazonia and the Atlantic Forest, supported by our historical demographic study of B. bilineatus , was recovered by previous studies based on genetic data of birds and lizards (Batalha‐Filho et al., ; Prates et al., ). Phylogeographic studies have also found evidence of northern colonizations between the Atlantic Forest and northeastern Amazonia (Batalha‐Filho et al., ; Costa, ; Prates, Rivera, et al., ; Prates, Xue, et al., ). In spite of these two distinct proposed connection routes, previous studies have, by and large, found that Amazonia acted as the source of colonizations into the Atlantic Forest.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have emphasized the role of biological attributes in the idiosyncratic responses of different species to shared environmental changes, even between codistributed taxa (Garg et al, ; Prates, Rivera, Rodrigues, & Carnaval, ; Prates, Xue et al, ; Smith et al, ). It has been shown that differences in habitat choice and ecological constraints can explain variation in the levels of population divergence across taxa (Burney & Brumfield, ; Garg et al, ; Harvey et al, ; Smith et al, ; Weir, Bermingham, & Schluter, ).…”
Section: Discussionmentioning
confidence: 99%
“…A history of past forest connections and separation has been invoked to explain presently disjunct distributions in a variety of organisms (Birds: Batalha‐Filho et al, ; Mammals: Costa, ; Nascimento, Bonvicino, Oliveira, Schneider, & Seuãnez, ; Pavan, Martins, Santos, Ditchfield, & Redondo, ; Lizards: Pellegrino et al, ; Rodrigues et al, ; Prates et al, ; Prates, Rivera, et al, ; Prates, Xue, et al, ; Prates et al, , 2018; Snakes: Zamudio & Greene, ; Dal Vechio et al, ). However, studies based on genetic data have found incongruent times, spatial routes and directionalities of forest colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of past range expansions across South American rain forests has received increased attention. Proposed historical corridors between Amazonia and the Atlantic Forest include northern bridges through the dry Caatinga in present‐day north‐eastern Brazil and along Brazil's northern coast (Mammals: Costa, ; Lizards: Pellegrino, Rodrigues, Harris, Yonenaga‐Yassuda, & Sites, ; Prates, Rivera, et al, , Prates, Xue, et al, ; Birds: Batalha‐Filho, Fjeldsa, Fabre, & Miyaki, ; Snakes: Puorto et al, ; Dal Vechio et al, ), as well as southern bridges between south‐western Amazonia and the southern Atlantic Forest (Mammals: Costa, ; Lizards: Prates et al, ; Birds: Batalha‐Filho et al, ; Snakes: Dal Vechio et al, ). These forest corridors may have been established at different times in the past, with evidence of northern connections during the Pleistocene and southern ones over the Miocene (Batalha‐Filho et al, ; Dal Vechio et al, ; Ledo & Colli, ; Prates et al, ; Prates, Rivera, et al, ).…”
Section: Introductionmentioning
confidence: 99%